Acute and subchronic exposure to urban atmospheric pollutants aggravate acute respiratory failure in infants - Amanda Barbosa Neto; Alexandre A. Ferraro; Sandra E. Vieira (Scientific Reports, 2023)
Abstract Urban air pollution is a major factor that affects the respiratory health of children and adolescents. Less studied is exposure during the first two years of life. This study analyzed the influence of acute and subchronic exposure to urban air pollutants on the severity of acute respiratory failure (ARF) in the first two years of life. This population-based study included 7364 infants hospitalized with ARF. Acute exposure was considered to have occurred 1, 3 and 7 days before hospitalization and subchronic exposure was considered the mean of the last 30 and 60 days. We found that for acute exposure, significant increases in days of hospitalization (LOS) occurred at lag 1 day for NO2 (0.24), SO2 (6.64), and CO (1.86); lag 3 days for PM10 (0.30), PM2.5 (0.37), SO2 (10.8), and CO (0.71); and lag 7 days for NO2 (0.16), SO2 (5.07) and CO (0.87). Increases in the risk of death occurred at lag 1 day for NO2 (1.06), SO2 (3.64), and CO (1.28); and lag 3 days for NO2 (1.04), SO2 (2.04), and CO (1.19). Subchronic exposures at 30 and 60 days occurred for SO2 (9.18, 3.77) and CO (6.53, 2.97), respectively. The associations were more pronounced with higher temperatures and lower relative humidity levels. We concluded that acute and subchronic exposure to higher atmospheric concentrations of all the pollutants studied were associated with greater severity of ARF. The greatest increases in LOS and risk of death occurred with hot and dry weather.